Pragmatisme Politik: Studi Kasus Proses Rekrutmen Politik PDIP Pada Pilkada, Kabupaten Sleman - Helmi Mahadi (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2011)
This research will explains on candidate recruitment of major in Sleman that conducted by PDI-P and their behavior. This research uses a case study method through in-depth interviews and written documentation. The result shows that the failure of PDI-P Sleman in carrying internal candidate from the party is due to the occurrence of political pragmatism. In this context, pragmatism comes from two things. Firstly, internal factor is the failure of the PDI-P cadre of Sleman and the phenomenon of money as a determinant of recruitment of candidates. Secondly, external factor is the political culture of society that do not directly influence through elite perceptions about public preferences.